Transparency and Public Involvement in Animal Research. Issue 2 (May 2016) - Pound, Pandora; Blaug, Ricardo
To be legitimate, research needs to be ethical, methodologically sound, of sufficient value to justify public expenditure and be transparent. Animal research has always been contested on ethical grounds, but there is now mounting evidence of poor scientific method, and growing doubts about its clinical value. So what of transparency? Here we examine the increasing focus on openness within animal research in the UK, analysing recent developments within the Home Office and within the main group representing the interests of the sector, Understanding Animal Research. We argue that, while important steps are being taken toward greater transparency, the legitimacy of animal research continues to be undermined by selective openness. We propose that openness could be increased through public involvement, and that this would bring about much needed improvements in animal research, as it has done in clinical research.